Perubahan Upacara Sayur matua pada Masyarakat Simalungun di Desa Saribu Dolok, Kecamatan Silimakuta, Kabupaten Simalungun - Situmorang, Daniel Adjinegara; Hutajulu, Rithaony; Gulo, Hubari (Mahesa Research Center, 2025)
This study aims to analyze changes in the implementation of the Sayur Matua death ceremony in the Simalungun community in Saribu Dolok Village, Silimakuta District, Simalungun Regency. The method used is a qualitative approach with an in-depth interview technique with one key informant, namely Mr. Simarmata, a community leader who understands local traditions. The results of the study show that the implementation of the Sayur Matua ceremony has undergone various changes, both in terms of structure, symbols, and meaning. These changes are influenced by several main factors, including modernization, the entry of foreign culture, and shifts in social values among the younger generation. Traditional elements such as Gonrang Sipitu-pitu are still retained, although in a simpler form and not as complete as before. These findings show that there is a dynamic between cultural preservation and the need to adapt to the times. This research is expected to be a contribution to the study of local culture, as well as a consideration in efforts to preserve intangible cultural heritage, especially in the context of the Simalungun indigenous people.